Comparison of Beighton score and Brighton Criterion in order to diagnosis of joint hypermobility in children - Oksana Kulik; Magdalena Gębska (Kazimierz Wielki University, 2018)
Introduction Joint hypermobility is a rarely diagnosed condition, mostly because it's symptoms are frequently overlooked, usually because there is no proper and unequivocal diagnostic method. Joint hypermobility can lead to serious health issues, especially if the proceeding with this ailment is inapropriate. Underdiagnosis of this condition makes prevention of complications impossible in most cases. Currently, Beighton and Brighton are one of the most frequently used scores in joint hipermobility diagnostic. The tests are based on the same joints hipermobility assessment, but Brighton scale is extended by few more health issues, hence the results may diverge. Aim The main purpose of the study was to assess the prevalence of joint hypermobility in children using the Beighton and Brighton scores. The additional aim was to compare the diagnostic sensitivity of both scales. Materials and methods The study covered a group of 102 students (60 boys, 42 girls) aged between 6 to 11 years. A questionnaire was given to all children. Body height and weight measurements, hip and waist circumference measurements (WHR index) were also performed. In order to determine the occurrence of joint hypermobility in children, two standardized diagnostic tests were carried out: the Beighton score and the Brighton score. Results There was a statistically significant difference (p≤0.05) in the results of the Beighton and Brighton test based on the number of points obtained by the subjects, which is noticeable in the results. According to the Beighton test 35 children suffer from hypermobility. On the contrary according to the Brighton score hypermobility was observed only in one examined child (a boy). Conclusions The occurrence of joint hypermobility in children using the Beighton score is higher than using the Brighton criteria. The Beighton score and Brighton's criteria are not well correlated, therefore the methods for diagnosing hypermobility should be improved.